The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.7314/apjcp.2012.13.4.1151
|View full text |Cite
|
Sign up to set email alerts
|

High-risk Human Papillomavirus Genotype Detection by Electrochemical DNA Chip Method

Abstract: According to a cohort study, HPV cumulative incidence rates are associated with younger women, certain ethnic groups and high frequency of alcohol consumption. Forty-three percent of women, who had attended at least one follow-up visit, were HPV negative. The incidence tended to decrease by 20% in the first year, 14% and 9% in the second and third years, respectively. The median duration of HPV infection was 8 months. 70% of women were no longer infected one year after the incident and 9% continued to be infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…In comparison with this study, Damin et al (2007), Chen et al (2012) and Burnett-Hartman et al (2013) found HPV-16 as the most frequently detected HPV type in patients with CRC. Therefore, this study supports the hypothesis that expresses the different frequency patterns of HPV infection according to geographical variations and ethnicity of the populations (Jung et al, 2004;Chansaenroj According to Table 3, analysis of medical data in infected patients with CRC in compare to non-infected patients with CRC explained a possible association between high-risk types of HPV infections and accession Gillison and shah (2003), Chen et al (2012), Hamid and Mustafa (2012), Ghasemian et al (2013), Zandberg et al (2013) in comparison with results from Motlagh et al (2007), Giuliani et al (2008) investigate the ability of HPV infection to induce advanced stages of cancer in different malignancies. Furthermore, this study highlights the impact of high-risk types of HPV infection in distant metastasis and malignant lymph nodes invasion in compare with non-infected patients, which have been previously reported in several investigations (Chen et al, 1993;Gillison and shah, 2003;Bognar et al, 2008;McHugh et al, 2009;Zandberg et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…In comparison with this study, Damin et al (2007), Chen et al (2012) and Burnett-Hartman et al (2013) found HPV-16 as the most frequently detected HPV type in patients with CRC. Therefore, this study supports the hypothesis that expresses the different frequency patterns of HPV infection according to geographical variations and ethnicity of the populations (Jung et al, 2004;Chansaenroj According to Table 3, analysis of medical data in infected patients with CRC in compare to non-infected patients with CRC explained a possible association between high-risk types of HPV infections and accession Gillison and shah (2003), Chen et al (2012), Hamid and Mustafa (2012), Ghasemian et al (2013), Zandberg et al (2013) in comparison with results from Motlagh et al (2007), Giuliani et al (2008) investigate the ability of HPV infection to induce advanced stages of cancer in different malignancies. Furthermore, this study highlights the impact of high-risk types of HPV infection in distant metastasis and malignant lymph nodes invasion in compare with non-infected patients, which have been previously reported in several investigations (Chen et al, 1993;Gillison and shah, 2003;Bognar et al, 2008;McHugh et al, 2009;Zandberg et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The electrochemical DNA chip can detect single and multiple infections of high risk genotypes of HPV with higher sensitivity, specificity, rapidity and simplicity when compared with other methods such as direct sequencing (Hagiwara et al, 2007). Other studies have also demonstrated good agreement in electrochemical DNA chip testing when compared to direct sequencing (Chansaenroj et al, 2012;Satoh et al, 2013).…”
Section: Introductionmentioning
confidence: 79%
“…The automated hybridization of probe and primer and the subsequent quantification of the resulting electrochemical signals was done on the GLH-2C601 Genelyzer TM (Toshiba, Tokyo, Japan). A previous study done in our lab using the same electrochemical DNA chip reported no cross hybridization (Chansaenroj et al, 2012).…”
Section: Pathological Classification Of Cytological Findingsmentioning
confidence: 95%
“…HPV detection using the TOSHIBA DNA chip was performed according to manufacturer’s instructions [32]. Briefly, 200–500ng of gDNA were denatured at 95°C for 5 min, and then added into each of the 6 loop-mediated isothermal amplification (LAMP) reaction tubes.…”
Section: Methodsmentioning
confidence: 99%